Influence of chilling-and-reheating pasta on postprandial glycemic responses and appetite: a randomized control trial - Alhussain, Maha H.; Almousa , Areej A; Alarifi , Sehad N; AlSedairy, Sahar Abdulaziz; Alhowikan , Abdulrhamn M (Progress in Nutrition, 2022)
Background and aim: Starch chilling-and-reheating process can affect starch structures and digestibility. Studies investigating the potential health implications of this process are lacking. We aimed to examine the influence of chilling-and-reheating pasta, a starchy food, on postprandial glycemic and insulinemic responses, as well as appetite. Methods: Eight healthy young males participated in this randomized cross-over study. Subjects were provided pasta meals in the laboratory after overnight fasting on two separate occasions, at least 1 week apart. On each laboratory visit, subjects were given either freshly cooked pasta, as a control meal (CM) or cooked, overnight chilled, and reheated pasta as a test meal (TM). The two meals (CM and TM) were isocaloric and matched for composition, ingredients, and amount. Blood samples and subjective appetite ratings were collected at fasting and for a period of 3-h after meal consumption. Results: TM significantly increased net incremental area under the curve (net iAUC) for satiety (mean ± SD: TM: 10181.25±3140.65 mm; CM: 7132.37±3187.31 mm; p = 0.03) and reduced the desire to eat (TM: −8190.75±4333.34 mm vs. CM: −4594.50±1481.11 mm; p = 0.03). However, no significant differences were found in postprandial glycemic and insulinemic responses between the two meals. Conclusions: Chilling-and-reheating pasta was associated with greater satiety and a lower desire to eat and, in a long term, may lead to weight management.